FILSAFAT PERPUSTAKAAN DALAM PERSPEKTIF UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 43 TAHUN 2007: ANALISIS DAN IMPLIKASI - Setiyono, Joko (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
The philosophy of libraries serves as an essential conceptual foundation for the development and management of libraries as information institutions. This paper discusses the evolution of the library concept within the framework of Undang-Undang Nomor 43 Tahun 2007, as well as the core principles underlying library philosophy, such as open access, intellectual freedom, and information literacy. Through a historical approach and theoretical analysis, this paper identifies the role of libraries as agents of social change and cultural preservation, highlighting the challenges and future prospects in the digital age. The main findings indicate that modern libraries are not only centers for information storage but also collaborative learning and innovative spaces that facilitate social transformation. The conclusions emphasize the importance of maintaining the fundamental values of libraries, in accordance with the mandate of Undang-Undang Nomor 43 Tahun 2007, amidst technological advancements and societal dynamics.